BACK PAIN IN THE ELDERLY – APPROACHES TO THE DIAGNOSIS AND TREATMENT - N. A. Shostak; N. G. Pravdyuk; N. V. Shvireva; V. A. Egorova (Klinicist)
The main approaches to diagnosis and treatment of pain in the back of the elderly are presented. The main place is given to varieties of mechanical pain. Clinical features of non-traumatic compression of the vertebrae, approaches to the diagnosis ostheoporosis fractures are described. The problem of the differential diagnosis of infectious, neoplastic, metabolic damage of the spine is discussed. The main therapeutic approaches to the therapy of acute mechanical back pain are identified.